2001
DOI: 10.1111/j.1349-7006.2001.tb01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Transforming Growth Factor‐(β Signaling Pathway in Hepatocellular Carcinomas Induced Endogenously and Exogenously in Rats

Abstract: To elucidate involvement of the transforming growth factor-β β β β (TGF-β β β β) ) ) ) signaling pathway in endogenous and exogenous liver carcinogenesis, we investigated mutations of TGF-β β β β receptor type II (TGF-β β β βRII), Smad2 and Smad4 genes, and expression of TGF-β β β βRII in hepatocellular carcinomas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Moreover, we have recently found that there are differences between exogenous and endogenous mechanisms underlying rat hepatocarcinogenesis. 30,31) However, the present results showed that the decreased Bcl-x expression was observed in the experimental models with both DEN and CDAA diet, which have been widely used in studies on hepatocarcinogenesis, suggesting that, similar to the increase in GST-P protein, the decrease in Bcl-x protein may be a common event for at least rat preneoplastic lesions induced exogenously and endogenously. The appearance of preneoplastic cells with decreased Bcl-x expression also seems to be more delayed than that of the increased GST-P expression.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, we have recently found that there are differences between exogenous and endogenous mechanisms underlying rat hepatocarcinogenesis. 30,31) However, the present results showed that the decreased Bcl-x expression was observed in the experimental models with both DEN and CDAA diet, which have been widely used in studies on hepatocarcinogenesis, suggesting that, similar to the increase in GST-P protein, the decrease in Bcl-x protein may be a common event for at least rat preneoplastic lesions induced exogenously and endogenously. The appearance of preneoplastic cells with decreased Bcl-x expression also seems to be more delayed than that of the increased GST-P expression.…”
Section: Discussionmentioning
confidence: 50%
“…This indicates the possibility that the TGF-␤1 signaling pathway is disturbed in preneoplastic nodules induced by a CDAA diet [37,38]. TGF-␤1 is produced as a small, biologically inactive, latent complex, which consists of mature TGF-␤1 and latency-associated peptide (LAP).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that inactivation of the Smad4 gene might play a role in pancreatic cancer and possibly other human cancers. In the case of rodents, we previously reported a low frequency of Smad4 mutations in rat lung adenocarcinomas induced by N-nitrosobis(2-hydroxypropyl)amine (8.3%) (22) and no mutations in rat hepatocellular carcinomas induced by Nnitrosodiethylamine (29). The present study showed only one mutation in 12 hamster PDAs and three established cell lines.…”
Section: Discussionmentioning
confidence: 59%